Spatiotemporal Evolution of Urban Driving Factors and Seasonal Heat Island Response from the Perspective of Local Climate Zones: A Case Study of Xiamen City, China - Jinxin Wang; Liangliang Sheng; Tao Li (Remote Sensing)
Understanding the mechanisms driving the urban heat island (UHI) phenomenon is essential for urban sustainability. This study investigated the spatiotemporal dynamics and underlying factors of surface urban heat island (SUHI) in Xiamen. Utilizing the radiation conduction equation, we calculated surface urban heat island intensity (SUHII) for the summers and winters of 2003, 2005, 2010, 2015, and 2020, followed by spatial distribution analysis. The local climate zone (LCZ) method was employed to assess surface morphology and spatial structure in 2010 and 2020. Urban driving factors, including built-up areas, building height, gross domestic product (GDP) per capita, industrial structure, and population density, were analyzed using the Geodetector model to explore their influence on SUHI across seasons. Based on different LCZ types, a more detailed analysis was conducted on SUHI and the performance of influencing factors using Pearson’s correlation. Key findings indicate that (1) the proportion of SUHI areas in built-up LCZ types always exceeds that of natural LCZ types and is more pronounced in the summer than in the winter. (2) In built-up LCZ types, open mid-rise built (LCZ 5) showed the highest average proportion of SUHI areas in the summer (95.95%), and large low-rise built (LCZ 8) had the highest average proportion in the winter (95.28%). In natural LCZ types, bare rock or paved (LCZ E) had the highest average proportion of SUHI areas in both the summer (61.86%) and winter (51.26%), and water (LCZ G) had the lowest average proportion in the summer (6.16%) and winter (4.92%). (3) Significantly, building height and proportion of the secondary industry intensified the SUHI in the summer, with dynamic changes observed during the winter. This study provides more targeted insights into mitigating SUHI in Xiamen and other similar coastal cities.